Intra-Articular Steroid Injection for Patients with Hip Osteoarthritis: A Systematic Review and Meta-Analysis. (25th February 2020) - Zhong, Hui-Ming; Zhao, Guang-Feng; Lin, Tiao; Zhang, Xin-Xin; Li, Xin-Yu; Lin, Jun-Fan; Zhao, Si-Qi; Pan, Zhi-Jun
Abstract : Purpose . The aim of this current review was to confirm the efficacy of intra-articular steroid therapy (IAST) for patients with hip osteoarthritis (OA) and discuss the duration and influential factors of IAST. Methods . Online databases (Medline, EMBASE, and Web of Science) were searched from inception to May 2019. Both randomized controlled trials (RCTs) and noncontrolled trials assessing the efficacy of hip IAST on pain were included. Common demographics data were extracted using a standardized form. Quality was assessed on the basis of Oxford Centre for Evidence-Based Medicine 2011 Levels of Evidence. Results . 12 trials met the inclusion criteria. According to data from individual trials, IAST had significant efficacy on hip OA in both immediate and delay pain reduction, which persisted up to 12 weeks after IAST. The influences of the baseline severity of hip OA or synovitis and injection dose or volume on the clinical outcome of IAST were still controversial. The IAST appeared to be well tolerant by most of the participants. Conclusion . IAST was proved to be an efficacious therapy in both immediate and delay pain reduction for hip OA patients within 12 weeks. The longer follow-up data of efficacy and safety and potentially influential factors are still unclear and needed further confirmation.